Peningkatan Proses Dan Hasil Belajar Ipas Siswa Menggunakan Model Project Based Learning Pada Kelas V SD Negeri 89/II Lubuk Niur - Said Qolbi Khoirun (Master of Pedagogy and Elementary School Learning, 2026)
A learning mastery percentage of just 33.5% of pupils met the school's minimum mastery requirement (KKTP) of 70, indicating low student learning outcomes in IPAS topics. This classroom action research was carried out in Grade V at SDN 089/II Lubuk Niur. This study aimed to describe how the Project-Based Learning model in Grade V of SDN 89/II Lubuk Niur improved the IPAS learning process and results. Twelve kids served as the research subjects for this classroom action study. The researcher carried out this study in two cycles, each of which included planning, action implementation while observation was being made, and reflection at the conclusion of the cycle. The findings demonstrate how well the Project-Based Learning model was implemented and how it improved the fifth-grade students' IPAS process and learning outcomes. In cycle I, the teacher's observation results were 60%; in cycle II, they rose to 85%. In cycle I, the student observation rate was 50%; in cycle II, it rose to 83.33%. In cycle I, students' mastery of the IPAS learning outcomes was 66.66%; in cycle II, that number rose to 91.66%. This rise demonstrates that using the Project-Based Learning methodology can improve student engagement and comprehension of IPAS, particularly when it comes to Bumiku Sayang (My Beloved Earth). The research was ended in cycle II when the success indicators were met. Overall, fifth-grade students' IPAS learning process and results were improved by the implementation of the Project-Based Learning paradigm